Modeling Coparenting Quality Based on Marital Satisfaction, Emotional Intelligence, Parenting Alliance, and Psychological Flexibility - Batista, Yanelis; Bennett, Chloe; Escobar, Ricardo (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to develop and test a structural model of coparenting quality based on marital satisfaction, emotional intelligence, parenting alliance, and psychological flexibility among Canadian parents. Methods and Materials: This study employed a cross-sectional correlational design using structural equation modeling (SEM). The study population consisted of married or cohabiting parents residing in Canada who had at least one child between the ages of 3 and 16 years. A total of 624 parents were recruited through community organizations, educational institutions, parenting networks, and online platforms using convenience sampling. Data were collected using the Coparenting Relationship Scale (CRS), Revised Dyadic Adjustment Scale (RDAS), Wong and Law Emotional Intelligence Scale (WLEIS), Parenting Alliance Measure (PAM), and Acceptance and Action Questionnaire-II (AAQ-II). Descriptive statistics, Pearson correlation analysis, confirmatory factor analysis, and structural equation modeling were conducted using SPSS 29 and AMOS 29. Model fit was evaluated using χ²/df, CFI, TLI, GFI, AGFI, RMSEA, and SRMR indices. Findings: The results revealed significant positive correlations among all study variables. The proposed structural model demonstrated excellent fit to the data (χ²/df = 2.41, CFI = .96, TLI = .95, GFI = .94, AGFI = .92, RMSEA = .048, SRMR = .041). Structural path analysis indicated that parenting alliance was the strongest predictor of coparenting quality (β = .42, p < .001), followed by marital satisfaction (β = .34, p < .001), psychological flexibility (β = .18, p < .001), and emotional intelligence (β = .15, p < .001). Collectively, the predictor variables explained 68% of the variance in coparenting quality (R² = .68), demonstrating substantial explanatory power. Conclusion: The findings indicate that coparenting quality is significantly influenced by both relational and psychological factors. Parenting alliance and marital satisfaction emerged as particularly influential determinants, while emotional intelligence and psychological flexibility contributed additional explanatory value.